2022
DOI: 10.21203/rs.3.rs-1153467/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evidence of reduced academic performance among school children with helminth infection independent of nutritional status

Abstract: Background Soil transmitted helminths (STH) pose a formidable health risk to school-age children in resource-limited settings. Unfortunately, mass deworming campaigns have been derailed since the onset of the COVID-19 pandemic. The present study assessed the cross-sectional associations between STH, nutritional status and academic performance of school children in the Banda District of Ghana. Methods School children (5–16 years) (n=275) were recruited through both school and household visits by community hea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In this study, intestinal helminth infection was correlated with low academic performance. Studies in South Africa, Ghana and Egypt also showed lower academic performance in children infected with soil transmitted helminths compared to their non infected counterparts [ 25 , 26 , 52 ]. A meta-analysis of 15 studies also reported lower scholastic achievement/academic scores among children infected with Schistosoma and/or those not dewormed with praziquantel compared to uninfected ones [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, intestinal helminth infection was correlated with low academic performance. Studies in South Africa, Ghana and Egypt also showed lower academic performance in children infected with soil transmitted helminths compared to their non infected counterparts [ 25 , 26 , 52 ]. A meta-analysis of 15 studies also reported lower scholastic achievement/academic scores among children infected with Schistosoma and/or those not dewormed with praziquantel compared to uninfected ones [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, study findings on the relationship of helminth infection with undernutrition, anemia, and poor academic performance are mixed. While some studies reported increased risk of anemia [ 18 , 19 , 20 , 21 ], undernutrition [ 21 , 22 , 23 , 24 ], and poor academic performance [ 25 , 26 , 27 ] in children infected with helminths, several studies reported lack of relationship between infection with these parasites and anemia [ 28 , 29 ], undernutrition [ 30 , 31 ], and poor academic performance [ 32 ]. Even some studies showed lower odds of anemia and undernutrition among children infected with soil-transmitted helminths [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%